2015
DOI: 10.1111/jace.13815
|View full text |Cite
|
Sign up to set email alerts
|

Glass Formation and Ionic Conduction Behavior in GeSe2–Ga2Se3–NaI Chalcogenide System

Abstract: Series of glassy and glass‐ceramic samples in the GeSe2–Ga2Se3–NaI system is prepared by melt‐quenching technique and the glass‐forming region is well‐defined by XRD investigations. Na‐ion conduction behavior is systemically studied by impedance measurements. For the glasses in the series (100−2x)GeSe2–xGa2Se3–xNaI, ionic conductivities increased with increasing x, whereas the attributed activation energy of ion conduction decreases. The enhanced mechanism is discussed by employing Raman spectra. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…This result indicates an improved diffusion dynamics of Na + ions in Na-NaI anode compared with that of pristine Na anode with a formed SEI in carbonate electrolyte [45]. Meanwhile, Sodium iodide (NaI) is an ionic compound with an ionic conductivity of ~3 × 10 −2 S/cm, and it has been reported that the introduction of NaI can enhance the ionic conductivity of sodium solid electrolyte (1.6 × 10 −5 S/cm for 45Ge-Se 2 -25Ga 2 Se 3 -30NaI glass) [46]. In particular, NaI can also be combined with PEO for preparing high ionic conductivity polymer electrolyte (such as PEO-NaI, 5.21 × 10 −5 S/cm) [47,48].…”
Section: Resultsmentioning
confidence: 99%
“…This result indicates an improved diffusion dynamics of Na + ions in Na-NaI anode compared with that of pristine Na anode with a formed SEI in carbonate electrolyte [45]. Meanwhile, Sodium iodide (NaI) is an ionic compound with an ionic conductivity of ~3 × 10 −2 S/cm, and it has been reported that the introduction of NaI can enhance the ionic conductivity of sodium solid electrolyte (1.6 × 10 −5 S/cm for 45Ge-Se 2 -25Ga 2 Se 3 -30NaI glass) [46]. In particular, NaI can also be combined with PEO for preparing high ionic conductivity polymer electrolyte (such as PEO-NaI, 5.21 × 10 −5 S/cm) [47,48].…”
Section: Resultsmentioning
confidence: 99%
“…These binaries are generally used as synthesis precursors, e.g., M 2 S or M 2 Se in chalcogenide-based glassy electrolytes, or as additives (especially the halides) to improve the electrochemical performance of more complex electrolyte materials. [67][68][69][70] In all of these binary materials, the anion is fully reduced; therefore, further reaction with the metal anode cannot occur and they are all stable down to 0 V against M/M + .…”
Section: Materials Selectionmentioning
confidence: 99%
“…The linear dependence of log σ versus (1/T ) follows the Arrhenius law and indicates phase stability over the given temperature range. [20,27] The ionic conductivity of 45Sb 2 S 3 •55CuI glassceramic is more than two order of magnitude higher than that of 70Sb 2 S 3 •30CuI glass. Activation energy (E a ) of Cu + conduction was determined by using the Arrhenius equation and listed in Table 2.…”
Section: Resultsmentioning
confidence: 98%
“…In addition, fast Cu-ion conduction was also investigated in this glassy system, which is of guiding significance for future designing solid glassy electrolytes. [19][20][21][22]…”
Section: Introductionmentioning
confidence: 99%